Experimental design methodology for optimising catalytic performance of Ni/Ce/α-Al 2O 3 catalyst for methane steam reforming - Ruzinah, Isha; Williams, Paul. T (Taylor & Francis, 2012)
The performance of a Ni/Ce/a-Al2O3 catalyst was optimised using a central composite design methodology to enhance hydrogen production and methane conversion in the catalytic steam reforming of methane. The influence of temperature, the presence of weight per cent Ni and Ce in the a-Al2O3 catalyst support and steam/methane ratio on CH4 conversion and H2 production were investigated. A 27 full factorial central composite experimental design was applied to determine the optimal levels for each of the significant variables. A second order polynomial was derived by multiple regression analysis on the experimental data. The CH4 conversion and H2 production increased significantly when the temperature was raised for the catalyst with a 10 wt-% content of Ni. Steam addition improved the CH4 conversion and H2 production; however, this required a higher operating temperature. Using this methodology, the optimum experimental values of 93.1% CH4 conversion and 73.5 vol.-%H2 were obtained using a catalyst with 12 wt-%Ni and 7 wt-%Ce added into the a-Al2O3 support at an operating temperature of 896uC with a steam/methane ratio of 2:2. The application of experimental design methodology is an effective statistical technique for optimising multifactor experiments such as the catalytic steam reforming of methane. It also reduces time and cost for the investigation.